Role of Living Donor Liver Transplantation for Advanced Hepatocellular Carcinoma - Montenovo, Martin I. (Digestive Disease Interventions, 2020)
Hepatocellular carcinoma (HCC) is the sixth most common malignant tumor worldwide and the third leading cause of cancer-related death. Despite the significant progress that has been achieved with local therapies, treatment remains limited by impaired liver function and high rate of recurrence. The purpose of the manuscript is to describe the current status of using living donor liver transplantation in patients with advanced HCC.
Keywords: HCC; liver transplantation; living donation